The effect of remifentanil on hemodynamic changes and muscle spasticity in patients undergoing total abdominal hysterectomy: A double-blind randomized clinical trial study - Hasan Zabetian; Sarina Malekzadeh; Navid Kalani; Farideh Mogharab; Mohammad Rahmanian (Mashhad University of Medical Sciences, 2023)
Introduction: Hysterectomy means removing the uterus from the body, which requires reducing spasticity and abdominal muscle tone during this long-term surgery. The present study was conducted with aim to investigate the effect of remifentanil on hemodynamic changes and muscle spasticity in patients undergoing total abdominal hysterectomy.Methods: This double-blind randomized clinical trial study was conducted in 2022 on 24 patients referred to the operating room of Motahari Hospital in Jahrom city who underwent hysterectomy surgery. Patients were divided into two groups of remifentanil and control. Hemodynamic symptoms, bleeding rate, surgeon's satisfaction with abdominal muscle spasticity and the time of re-injection of muscle relaxant were evaluated. Data analysis was done using SPSS software (version 21) and ANOVA with repeated measures, Mann-Whitney and chi-square tests. P<0.05 was considered statistically significant.Results: The mean systolic, diastolic, mean arterial blood pressure and heart rate were not significantly different between the two groups during most of the examined times (P>0.05). There was no significant difference between the two remifentanil and control groups in the mean amount of bleeding at different times (P>0.05), surgeon's satisfaction with abdominal muscle spasticity at different times (P>0.05). The time needed to re-inject the muscle relaxant in the first and second injections was significantly longer in the remifentanil group than the control group (P<0.05); However, there was no significant difference between the two remifentanil and control groups in the third injection (P>0.05).Conclusion: The use of remifentanil during anesthesia did not have a significant effect on improving hemodynamic changes, bleeding rate and surgeon satisfaction, but delayed the need for additional doses of muscle relaxants. However, it is necessary to further investigate this drug in combination with inhalation gases in larger communities.